Fetomaternal outcome in eclampsia - Roy, Madhumita; Ayingbi, Laishram; Kom, Telen Thangkhojam; Akoijam, Usharani; Paul, Papiya; Singh, L. Ranjit; Das, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Eclampsia is the third most common cause of maternal mortality, after haemorrhage and infection in the developing countries. Majority of cases of eclampsia are young primigravidas. The reduction in both maternal and perinatal morbidity and mortality remains the yard stick of success in the management of eclampsia. Methods: A hospital based analytical cross-sectional study was conducted among the pregnant women with eclampsia admitted in the department of Obstetrics and Gynecology in Regional Institute of Medical Sciences, Imphal. The study was conducted for a period of one and half years from September 2018 to March 2020. Results: Fifty-five (55) patients in the age group between 21 and 25 years constitute the maximum percentage of eclampsia (67.3%). Forty-five (81.8%) cases were antepartum eclampsia, 2 (3.6%) were intrapartum eclampsia and 8 (14.5%) cases were postpartum eclampsia. Majority (78.2%) of the cases were primigravidae, which is comparable to other studies. As much as 23 (41.8%) of the cases presented at 32-37 weeks period of gestation. There were two maternal deaths (3.6%) due to eclampsia related complications. There were 13 (21.7%) perinatal deaths in this study, out of which 10 (16.7%) were still births and 3(5%) were early neonatal deaths. Conclusions: Eclampsia is still an important obstetric emergency in the community contributing to significant maternal and perinatal morbidity and mortality. Eclampsia may not develop de novo and as such, it is not always a preventable condition. Early detection and prompt intervention of complications is vital to ensure a healthy outcome for both mother and baby.